Acts of nomination in political communication - Pałuszyńska, Edyta (Name – style – text: A jubilee book dedicated to Professor Elżebieta Umińska-Tytoń, 2023)
The article deals with selected features of political communication. Its purpose is to analyze the means of secondary nomination in relation to persons, objects, human collectives, and the means of primary and secondary nomination in relation to names of human collectives and events. The author analyzes proper names and descriptions from the last 20 years, during which she observed the political discourse in the media. Representative examples are given in the article. The analysis of the entire material shows that the acts of nomination play an important role in political communication. They are used to build an image, shaping a positive attitude towards the object or its discredit. Secondary changes of names are not uncommon, which are a signal of a different position and polemics. Specific descriptions that identify individual objects but do not lose their motivation deserve special attention. Thanks to this, they perform a persuasive function.